Analisis Strategi Peningkatan Pengumpulan Zakat Pertanian: Di BAZNAS Kabupaten Serdang Bedagai - Humaira, Hilma; Widana, Gusti Oka (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to evaluate strategies for enhancing agricultural zakat collection in Serdang Bedagai Regency using the Business Model Canvas (BMC) approach and SWOT Analysis. The research focuses on the National Amil Zakat Agency (BAZNAS) of Serdang Bedagai Regency, which is tasked with managing and optimizing zakat collection. A descriptive qualitative method was employed, gathering data through in-depth interviews with BAZNAS personnel and direct observations of zakat collection practices. The findings indicate that the application of BMC enables BAZNAS to develop more innovative and efficient business models, thereby improving zakat collection, particularly for agricultural zakat. SWOT Analysis further highlights internal strengths and weaknesses, along with external opportunities and threats that BAZNAS faces in its zakat collection efforts. The study identifies several critical success factors, including active community participation, ongoing education, and strategic partnerships with various stakeholders. This research offers structured and practical recommendations for BAZNAS Serdang Bedagai to optimize agricultural zakat collection. The effective implementation of these strategies is expected to enhance the welfare of farmers and the wider community in Serdang Bedagai Regency through improved zakat management.